Micro-Electromechanical System-Based Parasitic Patch Antenna on Quartz Substrate for High Gain - Haoran Zhao; Qi Wang; Jianyu Du; Lang Chen; Wen Yue; Wei Wang (Sensors)
This paper presents a novel Ku-band parasitic patch antenna based on MEMS technology. The antenna consists of two substrates that are bonded together. The lower substrate houses the main patch and the ground layer, while the upper substrate supports the parasitic patch. To minimize the dielectric loss, the parasitic patch is fabricated using a double-layer suspended film process, combining parylene C and Spin-on-glass (SOG) materials. The two substrates are also bonded using SOG. The proposed antenna achieves a measured bandwidth of 30% (11.1~15.01 GHz), a peak gain of 8.57 dBi, and a compact size of 0.87 × 0.87 × 0.09 λ03.